NATIONALLY-ORIENTED APPROACH TO THE COMMUNICATIVE COMPETENCE DEVELOPMENT IN THE PROCESS OF TEACHING FOREIGN LANGUAGES - Grickevich, Julia; Luk’janova, Svetlana; Popkova, Larisa; Jakovleva, Anastasija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article is devoted to the conceptualization of the possibilities of a nationally-oriented approach in the development of communicative competence, particularly of sociocultural competence, in the process of teaching foreign languages. The article dwells upon the interdependence of students' national characteristics, the degree of tolerance to ambiguity and the results of language testing. The theoretical basis are works on the methodology of teaching foreign languages related to the development of communicative competence, as well as to the concept of “tolerance to ambiguity”. The authors of the article determine the ways, means, methods of forming the proper level of tolerance to ambiguity, and therefore, a tolerant attitude to the values of the carriers of another culture. Experimental data were obtained in the course of work with groups of Chinese and Turkmen students studying Russian as a foreign language at Pskov State University, as well as with the groups of Russian-speaking school graduates who took mock  International English Language Testing System [IELTS] in St. Petersburg, Novosibirsk and Pskov. A nationally-oriented approach in teaching foreign languages should be prioritized not only at the stage of preparation for language testing, but also in the development of test materials.